2006
DOI: 10.1021/pr050402b
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Approach to Comparing Whole-Cell Proteomes of Bacillus cereus Indicates a Biofilm-Specific Proteome

Abstract: Biofilm bacteria are widely held to exhibit a unique phenotype, typified by their increased resistance to antimicrobial agents. Numerous studies have been devoted to the identification of biofilm-specific genes, but surprisingly few have been reported to date. We compared the whole cell proteomes of 24 h old Bacillus cereus biofilms and the associated suspended population to exponential, transient and stationary phase planktonic cultures using the unbiased approach of principal component analysis, comparing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 52 publications
2
27
0
1
Order By: Relevance
“…5). These results are consistent with those reported for P. aeruginosa and B. cereus [16,17,35] which, based on multivariate proteomic approaches (PCA), indicated that biofilm formation has a distinctive and specific impact on the bacterial physiology compared to planktonic growth. However, in the past the existence of a biofilm specific physiology has been questioned based on microarray data.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…5). These results are consistent with those reported for P. aeruginosa and B. cereus [16,17,35] which, based on multivariate proteomic approaches (PCA), indicated that biofilm formation has a distinctive and specific impact on the bacterial physiology compared to planktonic growth. However, in the past the existence of a biofilm specific physiology has been questioned based on microarray data.…”
Section: Discussionsupporting
confidence: 92%
“…For example, a hypothetical spectrum of a cell mixture composed of 25% of a population A and 75% of a population B results from the following arithmetic operation applied to the FT-IR spectra: 0.256spec-trum condition A 1 0.756spectrum condition B. A similar approach was carried out to generate in silico mixed proteomes according to Vilain and Brözel [17]. In silico mixed spectra and proteomes were statistically analysed as described above.…”
Section: Multivariate Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This issue has been addressed in a number of recent studies. One study compared the proteome of Bacillus cereus grown under biofilm conditions with those of logarithmic-and stationary-phase planktonic cultures using principal-component analysis (335). The results of the analysis showed that the biofilm proteome was different from the stationary-phase proteome, arguing that biofilms are distinct from stationary-phase populations.…”
Section: Is There a Biofilm Fingerprint?mentioning
confidence: 99%
“…Similar observation has been made by the others (Seneviratne and Indrasena, 2006); Jayasinghearachchi and Seneviratne, 2006) where 8-13 fold increment of phosphorus solubilization was observed with biofilm application. This could be due to high level of organic acids production associated with biofilm community with high level of gene expression and it was different from their individual microbes present in the environment (Vilain and Brozel, 2006).…”
Section: Discussionmentioning
confidence: 96%